TESTS OF LOADING STRUCTURES OF A SPECIAL ROLLING STOCK AFTER LONG OPERATION (Transport systems and technologies, 2021)
Traffic safety is an essential requirement for railways. In order to ensure uninterrupted transportation of passengers and goods by rail by the enterprise of JSC "Ukrainian Railways", the task of ensuring the operation of rolling stock outside the assigned line of service remains urgent. Proceeding from this, it follows that it is necessary to carry out tests aimed at creating conditions for the operation of rolling stock while maintaining dynamic and strength characteristics. This article presents the order, scope and results of strength tests of rolling stock after long-term operation on the example of an AS1a-type railroad car. The results of the maximum stress levels, standard deviation, fatigue safety factors, the dependence of the stress level on the speed of movement are obtained. Based on the research results, a technical solution has been developed that allows using technical diagnostics methods to extend the service life of the AS1a type railroad cars after the end of the assigned service life.
Keywords: rolling stock, supporting structures, auto-rail, tests, strength, fatigue resistance, service life.